Cover Feature: Light‐Triggered Nitric Oxide Release by a Photosensitizer to Combat Bacterial Biofilm Infections (Chem. Eur. J. 17/2021). Issue 17 (22nd January 2021) - Zhao, Zhennan; Li, Huinan; Tao, Xuan; Xie, Yanxuan; Yang, Liang; Mao, Zong‐Wan; Xia, Wei
Abstract : Upon light irradiation, a novel dual‐functional ruthenium compound releases nitric oxide (NO) and reactive oxygen species (ROS). NO induces Pseudomonas aeruginosa biofilm dispersal and liberates bacteria. The free‐floating bacteria are subsequently sterilized by ROS. Therefore, the compound can readily eradicate mature biofilms at low concentration, which reduces cytotoxicity to mammalian cells. More information can be found in the Full Paper by Z.‐W. Mao, W. Xia, et al. on page 5453 .